Evaluation of urgent caesarian according to colour code at the Befelatanana University Hospital Centre of Obstetric Gynecology in Antananarivo Madagascar - Romuald, Randriamahavonjy; Besaina, Rakotozanany; Housni, Ibrahim; Martial, Rakotonirina; Tiphaine, Rakotoson Koloina; Andrianampanalirivo, Hery Rakotovao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Color code was described for the first time in 2003 was described for the first time in 2003 by since and al. The objective of this study was to accomplish urgent caesarian sections according to color code over delays indications-births (DIN) in Motherhood Befelatanana, Antananarivo, Madagascar. Methods: It was about a longitudinal prospective, analytical study of caesarian sections performed in emergency in CHUGOB going from June 1st till December 31st, 2017. Results: Authors took a census 193 caesarian sections of emergency. Among these patients 28 (14.50%) had a caesarian section encode red, 42 (21.76%) an orange code and 123 (63.73%) a green code. The medium age of the patients was of 26.4 years and that of the gestation was of 37SA and 6 days. The delay indication-birth (DIN) medium was of 102.9 minutes for red code, 99.7 minutes for orange code and 75 minutes for green code. Conclusions: Authors could not attain DIN of 30 minutes shape in international recommendations. Authors must improve the delay indication entered in the surgical unit by reinforcing knowledge of the agents of support on the management of emergency obstetrical. The possibility of leading to a very quick birth is an indisputable progress in obstetrics but she should not make forget risks inherent in such procedure.